Induction of the Gα(q) Signaling Cascade by the Human Immunodeficiency Virus Envelope Is Required for Virus Entry - Harmon, Brooke (American Society for Microbiology (ASM), 2008)
Binding of human immunodeficiency virus type 1 (HIV-1) envelope glycoprotein (Env) with the primary receptor CD4 and one of two coreceptors, CXCR4 or CCR5, activates a signaling cascade resulting in Rac-1 GTPase activation and stimulation of actin cytoskeletal reorganizations critical for HIV-1-mediated membrane fusion. The mechanism by which HIV-1 Env induces Rac-1 activation and subsequent actin cytoskeleton rearrangement is unknown. In this study, we show that Env-mediated Rac-1 activation is dependent on the activation of Gα(q) and its downstream targets. Fusion and Rac-1 activation are mediated by Gα(q) and phospholipase C (PLC), as shown by attenuation of fusion and Rac-1 activation in cells either expressing small interfering RNA (siRNA) targeting Gα(q) or treated with the PLC inhibitor U73122. Rac-1 activation and fusion were also blocked by multiple protein kinase C inhibitors, by inhibitors of intracellular Ca(2+) release, by Pyk2-targeted siRNA, and by the Ras inhibitor S-trans,trans-farnesylthiosalicylic acid (FTS). Fusion was blocked without altering cell viability or cell surface localization of CD4 and CCR5. Similar results were obtained when cell fusion was induced by Env expressed on viral and cellular membranes and when cell lines or primary cells were the target. Treatment with inhibitors and siRNA specific for Gα(i) or Gα(s) signaling mediators had no effect on Env-mediated Rac-1 activation or cell fusion, indicating that the Gα(q) pathway alone is responsible. These results could provide a new focus for therapeutic intervention with drugs targeting host signaling mediators rather than viral molecules, a strategy which is less likely to result in resistance.